Sistem Pendukung Keputusan Pemilihan Klinik Kecantikan Menggunakan Metode WASPAS - Dieo Alfiky Ananda; Yani Maulita; Suci Ramadani (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Beauty clinics are currently a primary need for women and men. This is proven by the increasing number of beauty clinics that are expanding in Binjai City. This makes consumers have to be more selective in choosing a beauty clinic so they don't have to waste a lot of time and money. Beauty Clinics are included in service businesses that aim to provide satisfaction for customers or consumers. With the emergence of various types of Beauty Clinics, competition between one Beauty Clinic and another has become increasingly fierce, thus encouraging each Beauty Clinic to try to improve the quality of its products and services.